2022
DOI: 10.1186/s12889-022-12555-9
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in non- coverage of full vaccination among children in Bangladesh: a comparative study of Demographic and Health Surveys, 2007 and 2017–18

Abstract: Background Vaccination is considered as a powerful and cost-effective weapon against many communicable diseases. An increase in full vaccination among the most vulnerable populations in Bangladesh was observed in the last decade. This study aimed to capture the socioeconomic inequalities in non-coverage of full vaccination among children aged 12–23 months using the nationally representative data from the Bangladesh Demographic and Health Surveys (BDHS). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Underserved and special setting populations receive fewer healthcare services, including immunization services; face economic constraints to bring their children to vaccination services areas; face cultural and/or linguistic barriers to accessing immunization healthcare services; lack familiarity with the healthcare delivery system and; live in locations where providers aren't readily available or physically accessible, such as pastoralist regions (1), developing regions (Afar, Somali, Gambella, and BG), newlyestablished regions of Sidama and South West Ethiopia Peoples' Region regions, con ict-affected areas (27), underserved urban population including slum areas (2), hard-to-reach areas in agrarian regions (Amhara, Oromia, and SNNP regions) (2), IDPs, and refugees.…”
Section: Variables and Operational De Nitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Underserved and special setting populations receive fewer healthcare services, including immunization services; face economic constraints to bring their children to vaccination services areas; face cultural and/or linguistic barriers to accessing immunization healthcare services; lack familiarity with the healthcare delivery system and; live in locations where providers aren't readily available or physically accessible, such as pastoralist regions (1), developing regions (Afar, Somali, Gambella, and BG), newlyestablished regions of Sidama and South West Ethiopia Peoples' Region regions, con ict-affected areas (27), underserved urban population including slum areas (2), hard-to-reach areas in agrarian regions (Amhara, Oromia, and SNNP regions) (2), IDPs, and refugees.…”
Section: Variables and Operational De Nitionsmentioning
confidence: 99%
“…The curves show that whether the socio-economic status related inequality in the outcome variable (on x-axis) prevails or not (27,32). If the curve is above the line of equality that means the index value is negative; hence it shows that the outcome variable is disproportionally concentrated among the poor and vice-versa (27,32). The concentration index is de ned as twice the area between the concentration curve and the line of equality.…”
Section: Data Management and Statistical Analysismentioning
confidence: 99%
“…Our results are generalizable to unvaccinated patients in Bangladesh and other low resource settings, as most of the Bangladeshi population was unvaccinated during the period of telehealth services. Although, current vaccination coverage is high in Bangladesh, coverage among vulnerable poor and elderly in rural areas are still low and the provision of boosters is inadequate now [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other South Asian countries, the vaccination coverage for children is the highest in Bangladesh [ 11 ]. Childhood vaccination prevents roughly 200,000 deaths in Bangladesh each year [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This reinforced the importance of a multisectoral approach in designing policies to achieve health-related sustainable development goals and universal immunization coverage in low- and middle-income countries. Several studies have been conducted in Bangladesh and other South Asian countries which identified sex of children [ 22 ], mother's age [ 5 , 11 ], mother's education [ 2 , 4 ], mother's employment status [ 5 ], mother's number of antenatal care visits [ 23 ], whether the delivery of child was at health facility [ 5 , 11 , 23 ], wealth status of household [ 2 , 13 , 24 ], household's size [ 2 , 5 ], and region of residence [ 4 ] as the influential factors behind childhood immunization. Although there are various studies in Bangladesh and other similar contexts vary, few studies focused on full vaccination of children from the age group 12-23 months.…”
Section: Introductionmentioning
confidence: 99%